Imperforate Hymen Presenting with Obstructive Urological And Gastrointestinal Symptoms in An Adolescent Girl: A Case Report - Prilly Astari; Airine Stefanie Lians (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Imperforate hymen is a rare congenital anomaly of the female genital tract caused by failure of hymenal membrane canalization during embryologic development. Although present at birth, it typically remains asymptomatic until adolescence, when obstruction of menstrual outflow leads to the accumulation of blood within the vagina (hematocolpos) or uterus (hematometra). In this case, the patient uniquely presented with urogenital obstruction symptoms, which can mimic primary urinary tract disorders and contribute to missed or delayed diagnosis. This highlights the importance of considering genital outflow tract anomalies in an adolescent female presenting with urinary complaints.Case presentation: A 13-year-old girl presented with cyclical lower abdominal pain, difficulty in micturition, and constipation for three months, without prior menarche. The physical examination showed mild abdominal distension with suprapubic tenderness. The inspection of the external genitalia showed a bulging hymenal membrane without an opening and without bluish discoloration, and pelvic ultrasonography showed hematometrocolpos. The patient underwent a hymenotomy, during which approximately 500 mL of retained menstrual blood was drained. This intervention resulted in complete resolution of symptoms, and the patient was subsequently discharged in stable condition.Conclusion: Careful genital examination is essential in adolescent female with primary amenorrhea and cyclical abdominal pain. Prompt diagnosis and surgical management result in excellent outcomes and prevent long-term morbidity.Himen Imperforata dengan Gejala Obstruktif Urologi dan Gastrointestinal Pada Remaja Putri: Laporan KasusAbstrakPendahuluan: Himen imperforate merupakan kelainan kongenital langka pada traktus genitalia perempuan yang disebabkan oleh kegagalan kanalisasi membran himen selama perkembangan embriologis. Meskipun sudah ada sejak lahir, kondisi ini sering kali tetap asimtomatik hingga masa remaja, ketika obstruksi aliran menstruasi menyebabkan hematokolpos atau hematometra. Pada kasus ini, pasien secara khas datang dengan gejala obstruksi urogenital yang dapat menyerupai gangguan saluran kemih primer sehingga berpotensi menyebabkan diagnosis terlewat atau terlambat. Hal ini menekankan pentingnya mempertimbangkan kelainan obstruksi traktus genitalia pada remaja perempuan dengan keluhan urinaria.Presentasi Kasus: Seorang anak perempuan usia 13 tahun datang dengan nyeri perut bawah siklik, sulit berkemih, dan konstipasi selama tiga bulan tanpa riwayat menarke. Pemeriksaan fisik menunjukkan distensi abdomen ringan dengan nyeri tekan suprapubik. Inspeksi genitalia eksterna tampak membran himen menonjol tanpa lubang dan tanpa perubahan warna kebiruan. Ultrasonografi pelvis menunjukkan hematometrokolpos. Pasien menjalani himenektomi dengan drainase ±500mL darah menstruasi yang tertahan. Gejala menghilang sepenuhnya dan pasien dipulangkan dalam kondisi stabil.Kesimpulan: Pemeriksaan genital yang teliti penting pada remaja dengan amenore primer dan nyeri perut siklik. Diagnosis dan tatalaksana dini memberikan hasil yang sangat baik.